MANAGEMENT OF SANITATION SIBOLGA FISHING PORT NORTH SUMATRA - Elkana Ritonga; Jonny Zain; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The study was conducted on 10 February to 26 February 2016. This study is intended to document the implementation and monitoring of fishing ports and sanitation problems. This study used a method of investigation. Data in tabular form the results of the research is conducted in the form of tables and descriptive by comparing the behavior or conditions that have been analyzed with national (NO 52A/KEPMEN-KP/2013) and international (Codex Alimentarius, 2009) standards. Based on the application of research results in sanitation Sibolga Fishing Port is good looks of infrastructure condition assessment by panelists, namely 66.7%, but the fish auction is still not good hygienic conditions, namely 44.4%. In the application of sanitary facilities at the fish auction in comparison with national and international provisions will be obtained from a percentage of the value of 25% to 41.6% for national and international. Difficulties in managing the auction sanitation and ecological areas in Sibolga Fishing Port is low awareness of users and visitors in the maintenance and monitoring of hygiene, so that some indicators were observed not met.Keyword : Sanitation, Sibolga Fishing Port, Fish Auction